3D skeletal movement-enhanced emotion recognition networks. (5th August 2021) - Shi, Jiaqi; Liu, Chaoran; Ishi, Carlos Toshinori; Ishiguro, Hiroshi
Abstract : Automatic emotion recognition has become an important trend in the fields of human–computer natural interaction and artificial intelligence. Although gesture is one of the most important components of nonverbal communication, which has a considerable impact on emotion recognition, it is rarely considered in the study of emotion recognition. An important reason is the lack of large open-source emotional databases containing skeletal movement data. In this paper, we extract three-dimensional skeleton information from videos and apply the method to IEMOCAP database to add a new modality. We propose an attention-based convolutional neural network which takes the extracted data as input to predict the speakers' emotional state. We also propose a graph attention-based fusion method that combines our model with the models using other modalities, to provide complementary information in the emotion classification task and effectively fuse multimodal cues. The combined model utilizes audio signals, text information, and skeletal data. The performance of the model significantly outperforms the bimodal model and other fusion strategies, proving the effectiveness of the method.